Somatometric charakterization of children from nursery schools at Bialystok - Jelisiejew, Tamara; Szewko-Szwaykowska, Irena (Anthropological Review, 1974)
Mean values of stature and weight of children aged 3 - 7 from nursery schools at Białystok have been presented. Altogether 395 children were examined this number comprised 205 boys and 180 girls. On the basis of the arithmetical mean (x), its error (Eχ) and standard square deviation (S) the behaviour of examined features in particular age groups was analysed and the obtained results compared with results got by other authors. This permitted to draw the conclusion that the children of Białystok as regards mean values of stature and weight have greatly surpassed the findings gathered from other parts of Poland, and among the compared series they have approached most closely to children from Toruń and Warsaw (1955 - 1965).